¿Voluntariado, compasión o autorrealización? - Béjar, Helena (Sociedad y Economía, 2006)
Although the everyday act of helping others seems to be most natural, in fact it is a social expression, assorted according to societies and historically dated in its specificity. Here we go into them in strict sociological terms, which involve the innovative implementation of interviews and use of various data sources. The result is substantiated in a complex musing on moral sentiments, individualism and modernity.